Analysis of the formation and development of the urban linear erosive features in Bauru /SP: Pinheiros Residential Case - Mariano, Guilherme; Battistelle, Rosane Aparecida Gomes; Furegatti, Simone Andrea (Technical and Scientific Journal Green Cities, 2021)
Erosive processes result from a combination of factors that are normally natural but due to the anthropic action it is aggravated and accelerated. Through this human interference, waterproofing and weakening the soil, rain erosion becomes the most evident, causing a large amount of sediment and increasing the speed of runoff (CORGHI, 2008). This causes flooding, silting of water courses, the appearance of erosive features. The present work aimed to identify the influencing factors in the formation and development of a feature located in Bauru. The data were filled out based on the Form for surveying conditioning factors and identifying erosive features, prepared by Mercaldi and Furegatti (2020). The erosion classification was given based on a table developed by Mercaldi and Furegatti (2019), who identified it as a gullet.  KEYWORDS: Anthropic action. Erosive processes. Gullet.